Minsan pa One moment more - Jeturian, Jeffrey (Manila MLR Films, 2005)
Jerry Toledo Jr. is an efficient and successful tour guide in Cebu, earning much from tour guide fees, tips from foreign tourists and hefty commisions on every local product that he endorses, including human products like female sex workers Aning and Minda. After his philandering father left his family for another woman, Jerry, being the eldest of the three children, had taken it upon himself to fill in the shoes of Jeremiah Sr. Acting now as the family bread winner, Jerry expects not only gratitude but also personal service from his brother and sister, whom he is sending to college. When Luna and Alex finally got married, Jerry knows he has been part of a great love story. Equipped with a better heart, Jerry also knows that he can pursue his own great love.
VCD
Jomari Yllana, Ara Mina, Chritian Vazquez
Keywords: Feature films